China, the PLA and Xi's ongoing purges: The corruption conundrum - Adam Perry MacDonald; Kurtis H. Simpson (Centre for International Governance Innovation (CIGI), 2025)
Chinese President Xi Jinping's extensive purges of senior leadership in the People's Liberation Army (PLA) are part of larger campaign to cement a personalist, centralized system of control over the Chinese Communist Party (CCP) and to reassert party authority over all aspects of the state and society. Despite more than a decade of continual prosecutions, the recent purging of some of the purportedly most loyal generals and admirals to Xi demonstrates continued deep institutional weaknesses and factionalism within the PLA, and that Xi continues to not wield complete authority over the institution. The persistence of such issues also raises questions about the PLA's operational coherence and its strategic reliability for the CCP more generally, both as a major element of and enabler furthering China's superpower ambitions, and, more importantly, effectively serving as the force of last resort in ensuring the CCP's survival in the face of potential internal or external challenges to its legitimacy. The authors say that while Beijing's rhetoric and threats of action against Taiwan remain aggressive, its actual willingness to initiate conflict may be more constrained than often predicted due to leadership issues. CCP-PLA relations in this age of persistent purges are a critical area for continued study, and a potential core indicator informing scenario considerations, the shaping of strategic responses and regional deterrence planning.
Keywords: 330